ОЦЕНКА ВОЗМОЖНОСТИ МЕТОДОВ АНАЛИЗА РАДИОНУКЛИДНОГО И ХИМИЧЕСКОГО СОСТАВА ПРИРОДНЫХ ВОД - Холов, Д.М.; Музафаров, А.М.; Холбоев, И. (SCIENCE and SOCIETY, 2020)
The article presents the results of evaluating the feasibility of methods for analyzing the radionuclide and chemical composition of natural waters. There are numerous chemical, physical, physico-chemical, and core-physical methods for analyzing the radionuclide and chemical composition of natural waters. In natural waters, in most cases it is determined - solids, pH values, anions - Cl-, NO2-, NO3-, СО32, HCO3-, SO42-, and their sum, cations - Ca+, Mg+, Na++K+, Fe3+, NH4 and their sum and concentration of metals Mn, Pb, Cu, Zn, Co, Cr, Ni.
Keywords: capabilities of methods; analysis methods; radionuclide composition; chemical composition; natural waters; chemical methods; physical methods; physicochemical methods; core physical methods; dry residue; pH values; anions and their sum; cations and their sum; concentration of metals